A new species of the deep-sea squat lobster genus Eumunida Smith, 1883 (Decapoda: Anomura: Eumunididae) from the Arabian Sea off southwestern India - Komai, Tomoyuki; Chakraborty, Rekha Devi; Paramasivam, Purushothaman; Gidda, Maheswarudu (Zootaxa, 2019)
A new species of the squat lobster genus Eumunida Smith, 1883 (Chirostyloidea: Eumunididae), E. multispina, is described and illustrated primarily on the basis of two male specimens from the Arabian Sea off the Kerala State, southwestern India, at depths of 250–400 m. One specimen from Lakshadweep, previously identified with E. funambulus Gordon, 1930, is also referred to the new species. The new species is morphologically most similar to E. funambulus among the 29 known congeners, but the presence of four epigastric spines and more numerous lateral spines on the carapace (four on the anterolateral and seven to 10 on the branchial margins) immediately distinguish the new species from E. funambulus. Genetic analysis using the mitochondrial COI and 16S rRNA markers also indicates that the new species is distinct from congenerics for which the sequence data are available.